A Descriptive study On Teaching Reading Narrative Text Using Short Stories To The Second Year Student Of SMP N 2 Colomadu - Riliana, Eka (2012)
This research aims at describing the process teaching reading narrative text using short stories at the second year of SMP N 2 Colomadu, The writer focuses on the process and the technique for teaching reading narrative using short stories at the second of SMP N 2 Colomadu especially in class VIII A in 2011/2012 academic year. The research uses descriptive qualitative research. The subject of research is the English teacher and the second year student of SMP N 2 Colomadu in teaching-learning process. The object of research is teaching- learning process of reading narrative text using short stories at SMP N 2 Colomadu.The data arein the formsof informant, and document. In this research the data are derived from event, information, and document. There are three techniques in collecting the data namely: interview, observation, and document. The results of the research show that 1.process of teaching reading narrative text using short stories at SMP N 2 Colomadu especially at the second year, includes three steps, namely: opening, study session, and closing. In opening; the teacher greeted, and checked the student's attendance. The second is study session; the teacher uses the four steps they are: Building Knowledge of Field (BKOF), Modeling of Text (MOT), Joint Construction of Text (JCOT), and Independent Construction of Text (ICOT). The last is closing, the teacher closed the meeting. The technique of teaching reading comprehension is: Read and Look up (silent reading) and Reading aloud.